Studi Fenomenologi : Pengalaman Keluarga terhadap Pemasungan dan Lepas Pasung pada Anggota Keluarga yang Mengalami Gangguan Jiwa di Wilayah Kerja Puskesmas Bantur Kabupaten Malang Propinsi Jawa Timur - Dwi Yogyo Suswinarto; Sri Andarini; Retno Lestari (STIKes Patria Husada Blitar, 2015)
The Confinenment action to the mental disordes suffer is the action done by the society to limitedÂ the sufferâ€™s mobilitas or activities its done based on the hopeless of the family whichÂ the medical effort can not made the suffer betterÂ than before. The economic burden is not small, additional with stigma from the society and the lessÂ optimal of mental health services base on family. Society and medicalâ€s crew.The result of this researchplore the family experience towar the confinement and re confinement of the disorderâ€™s family members in job area of Bantur Community health service of Malang Regency, East Java Province.The research methodology of this thesis use qualitative research (purposive sampling)about 6 sample. The process of data taking used the deep interview with semi structure helping by interview guide and fieldmemorize, its found 7 theme; 1) The cause of mental disorder, 2) The attitude change, 3) The Familyâ€™s comment on this situation, 4) The society stigma, 5) Confinement re confinement, 6) The confinement release, 7) The suffer family and society recovery.According the family conclusion the cause of disorder mental are pfisic condition and social pressure , and the moment of confinement â€“free-reconfinement happened of the society coment toward the situation stigma of the society and unoptimally the medical service. The free of confinement happened because of the family readiness,society and medical service and government involment. The rehabilition of the suffer after free from the confinement need the support from the family, society, community health service and related government.Â Â